Ultrastructure Organization of Collagen Fibrils and Proteoglycans of Stingray and Shark Corneal Stroma - Saud A. Alanazi; Turki Almubrad; Ahmad I. A. AlIbrahim; Adnan A. Khan; Saeed Akhtar (Journal of Ophthalmology)
We report here the ultrastructural organization of collagen fibrils (CF) and proteoglycans (PGs) of the corneal stroma of both the stingray and the shark. Three corneas from three stingrays and three corneas from three sharks were processed for electron microscopy. Tissues were embedded in TAAB 031 resin. The corneal stroma of both the stingray and shark consisted of parallel running lamellae of CFs which were decorated with PGs. In the stingray, the mean area of PGs in the posterior stroma was significantly larger than the PGs of the anterior and middle stroma, whereas, in the shark, the mean area of PGs was similar throughout the stroma. The mean area of PGs of the stingray was significantly larger compared to the PGs, mean area of the shark corneal stroma. The CF diameter of the stingray was significantly smaller compared to the CF diameter in the shark. The ultrastructural features of the corneal stroma of both the stingray and the shark were similar to each other except for the CFs and PGs. The PGs in the stingray and shark might be composed of chondroitin sulfate (CS)/dermatan sulfate (DS) PGs and these PGs with sutures might contribute to the nonswelling properties of the cornea of the stingray and shark.